Modern pancreatic islet encapsulation technologies for the treatment of type 1 diabetes - P. S. Ermakova; E. I. Cherkasova; N. A. Lenshina; A. N. Konev; M. A. Batenkin; S. A. Chesnokov; D. M. Kuchin; E. V. Zagainova; V. E. Zagainov; A. V. Kashina (Вестник трансплантологии и искусственных органов)
The review includes the results of analytical research on the problem of application of pancreatic islet encapsulation technologies for compensation of type 1 diabetes. We present a review of modern encapsulation technologies, approaches to encapsulation strategies, insulin replacement technologies: auto-, allo- and xenotransplantation; prospects for cell therapy for insulin-dependent conditions; modern approaches to β-cell encapsulation, possibilities of optimization of encapsulation biomaterials to increase survival of transplanted cells and reduce adverse consequences for the recipient. The main problems that need to be solved for effective transplantation of encapsulated islets of Langerhans are identified and the main strategies for translating the islet encapsulation technology into medical reality are outlined.